Knowledge, adherence and control among patients with hypertension attending a peri-urban primary health care clinic, KwaZulu-Natal - Olumuyiwa A. Olowe; Andrew J. Ross (AOSIS, 2017)
Background: Despite hypertension being a common condition among patients attending primary health care (PHC) clinics, blood pressure (BP) control is often poor. Greater insight into patient-related factors that influence the control of hypertension will assist in the development of an intervention to address the issues identified. Aim: The aim of the study was to assess patient-related variables associated with hypertension control among patients attending a peri-urban PHC clinic. Setting: The setting for this study was a peri-urban PHC clinic in KwaZulu-Natal. Method: This was an observational, descriptive and cross-sectional study with 348 patients selected over a 1-month period. A validated questionnaire was used to collect data on patients' hypertension knowledge and self-reported adherence, and BP recordings from their medical record were recorded to ascertain control. Results: Of the 348 participants, only 49% had good BP control and 44% (152/348) had concurrent diabetes mellitus. The majority of patients had moderate levels of knowledge on hypertension and exhibited moderate adherence. There was a significant relationship between knowledge and reported adherence, between reported adherence and control, but not between reported knowledge and control. Conclusion: Despite over 90% of the study population having moderate knowledge, and 62% with moderate reported adherence, BP was well controlled in only less than 50% of the study population. These findings suggest a need to emphasise adherence and explore new ways of approaching adherence.